Fiber twist-based wavelength tunability in tapered optical fiber filters - Mansor, Maisarah (Universiti Putra Malaysia Press, 2020)
This work demonstrates the tunability of tapered single mode fiber (SMF) and tapered polarization maintaining fiber (PMF) filters based on fiber twisting method. One end of the tapered fiber was twisted from 0o until 100o using the Vytran Fiber Processing System. Observation on the spectral output shows that the fiber twisting technique is a viable option to impart tunability in tapered fibers with total shift of 15 and 10 nm, respectively for SMF and PMF. Better tunability is observed in the SMF filter due to its simple physical structure and more straightforward interferometry effect but a significantly higher extinction ratio is observed for the PMF filter. Both filters exhibited region of linear wavelength shift with corresponding R2 values of 0.9924 and 0.9294 for SMF and PMF. The simplicity and reliability of the filter may pave the way for the development of a practical and compact tunable all-fiber filter for laser systems.